Groups with small cocentralizers - Javier Otal; Semko, N.N. (Algebra and Discrete Mathematics, 2009)
Let G be a group. If S⊆G is a G-invariant subset of G, the factor-group G/CG(S) is called the cocentralizer of S in G. In this survey-paper we review some results dealing with the influence of several cocentralizers on the structure of the group, a direction of research to which Leonid A. Kurdachenko was an active contributor, as well as many mathematicians all around the world.